Advancing the automation of plant nucleic acid extraction for rapid diagnosis of plant diseases in space - Haveman, Natasha J.; Schuerger, Andrew C.; Yu, Pei-Ling; Brown, Mark; Doebler, Robert; Paul, Anna-Lisa; Ferl, Robert J. (Frontiers in Plant Science, 2023)
Human space exploration missions will continue the development of sustainable plant cultivation in what are obviously novel habitat settings. Effective pathology mitigation strategies are needed to cope with plant disease outbreaks in any space-based plant growth systems. However, few technologies currently exist for space-based diagnoses of plant pathogens. Therefore, we developed a method of extracting plant nucleic acid that will facilitate the rapid diagnosis of plant diseases for future spaceflight applications. The microHomogenizer(TM) from Claremont BioSolutions, originally designed for bacterial and animal tissue samples, was evaluated for plant-microbial nucleic acid extraction. The microHomogenizer(TM) is an appealing device in that it provides automation and containment capabilities that would be required in spaceflight applications. Three different plant pathosystems were used to assess the versatility of the extraction process. Tomato, lettuce and pepper plants were respectively inoculated with a fungal plant pathogen, an oomycete pathogen, and a plant viral pathogen. The microHomogenizer(TM) along with the developed protocol proved to be an effective mechanism for producing DNA from all three pathosystems, in that PCR and sequencing of the resulting samples demonstrated clear DNA-based diagnoses. Thus, this investigation advances the efforts to automate nucleic acid extraction for future plant disease diagnosis in space.